Pengembangan Sistem Pengendali Kursor Menggunakan Sinyal Elektrookulogram (EOG) - Hasbian Fauzi Perdana; Fiky Yosef Suratman; Achmad Rizal (JTIM : Jurnal Teknologi Informasi dan Multimedia, 2019)
Amyotrophic Lateral Sclerosis (ALS) is an illness due to lack of nourishment in human motoric nerves. This illness causes the sufferer a loss in motoric movement. Thankfully there is still an organ that move well regardless the illness, and that is eye movement. Eye tracking method have been applied to controlling computer. Majority of eye tracking methods are divided into two methods, video-oculography (VOG), and electrooculography (EOG). VOG used camera as video recorder and processed using image processing to track eye movement. EOG used skin electrode that were usually used in electrocardiography, which could detect electrical activity on the back of eye. The principle in this research is to design a cursor controlling system using EOG sensor and classified the signal using simple thresholding method. The result would be cursor movement based on eye movement. Purpose of this final assignment is to design a cursor controlling system based EOG sensor. The experimental results yield an accuracy of 98% for the cursor movement controlling. The system can control the direction of the cursor's movement but cannot control other activities of the cursor.